A Unified Frame Work to Integrate Hadoop and IOT to Resolve the Issues of Storage, Processing with Leveraging Capacity of Analytics - Syam Prasad, Gudapati; Rajesh, P; Wasim Akram, Sk (International Journal of Engineering and Technology, 2018)
The new trend in the research and real time applications is Internet of Things (IOT). The functional benefits of IOT are ranging from smart house to smart cities. The main purpose of IOT is to integrate various devices logically and interacting between the devices without human intervention. The current discussion mainly focuses on leveraging the capacity of analytics in IOT and resolves the storage issues of the bulk data generated by IOT. The proposed idea gives the usage of Hadoop platform to store the data and from that data performing analytics for the sake of better utilization of IOT communications. The importance is explained with some real time scenarios where there is perfect blend of Hadoop platform and IOT. To store the various categories of the data Hadoop Distributed File System (HDFS) can be used, and to ingest the data from external platforms we can make use of Sqoop or Flume. The data available in HDFS can be used to process with the usage of Map Reduce (MR)technique. Once the data is available inÂ HDFS the analytics can be performed with Hive, Pig or R in the context of Machine learning or data mining techniques. The outcome of the proposed idea is integration of Hadoop and IOT platforms with a unified frame work which accommodates the integration of Hadoop and IOT, storage provisions to handle bulk data, processing of the stored data and applying analytics so as to effectively serve various stake holders.Â Â Â